PULMONER FUNCTION TESTS IN YOUNG PATIENTS WITH FIBROMYALGIA - Ali Gür,; Mehmet Karakoç,; Abdurrahman Şenyiğit,; Kemal Nas,; Remzi Çevik,; Ferda Erdoğan,; Ayşegül Jale Saraç, (Archives of Rheumatology, 2001)
Fibromyalgia is a painful syndrome of nonarticular origin, unknow etiology, characterized by generalized musculoskeletal pain, multiple tender points at characteristic locations, fatigue, stiffness, sleep disturbance, and anxiety. The aim of the present study was to assess the pulmonary function tests in young patients with fibromyalgia syndrome. 38 patients fulfilling the American College of Rheumatology classification criteria for fibromyalgia and 23 healthy volunteers of the same age range and sex were included in the study. All the subjects were nonsmokers. Pulmonary functions test included: forced vital capacity (FVC), first second forced expiratory volume (FEV1), FEV1/FVC, mid expiratory flow rate (FEF 25-75), FEF 25, FEF 50, FEF 75 and peak expiratory flow (PEF). Compared with the control group, all the spirometric values among the patients group were found to be relatively low although not significant, except FEV1, FVC, PEF, and FEF 25 which were significantly decreased (p < 0.05). This results indicated restrictive pulmonary disorder. Our results suggest that restrictive pulmonary disorder observed in fibromyalgia patients may be related to severe pain, fatigue, physical inactivity and respiratory muscle weakness.